2020
DOI: 10.1021/acs.molpharmaceut.0c00026
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Tetrandrine-hydroxypropyl-β-cyclodextrin Inclusion Complexes for Pulmonary Fibrosis Treatment

Abstract: Pulmonary fibrosis (PF) is a kind of interstitial lung disease with the features of progressive and often fatal dyspnea. Tetrandrine (TET) is the major active constituent of Chinese herbal Stephania tetrandra S. Moore, which has already applied clinically to treat rheumatism, lung cancer, and silicosis. In this work, a tetrandrine-hydroxypropyl-β-cyclodextrin inclusion compound (TET-HP-β-CD) was developed for the treatment of pulmonary fibrosis via inhalation administration. TET-HP-β-CD was prepared by the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…In addition, pulmonary delivery results in minimal systemic exposure and systemic side-effects, allows for high drug concentration in the lung and frequent administration, properties ideal for an anti-cancer drug delivery. Recently, Su et al have reported the formulation of tetrandrine-hydroxy propyl methyl cellulose complex for the treatment of bleomycin-induced pulmonary fibrosis in a murine model and observed excellent accumulation of the complex in the lungs after aerosol delivery [ 12 ]. Other studies report the ability of CDs to enhance pulmonary absorption where relative impermeability of the lungs to several drugs is posing a major obstacle after pulmonary delivery [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pulmonary delivery results in minimal systemic exposure and systemic side-effects, allows for high drug concentration in the lung and frequent administration, properties ideal for an anti-cancer drug delivery. Recently, Su et al have reported the formulation of tetrandrine-hydroxy propyl methyl cellulose complex for the treatment of bleomycin-induced pulmonary fibrosis in a murine model and observed excellent accumulation of the complex in the lungs after aerosol delivery [ 12 ]. Other studies report the ability of CDs to enhance pulmonary absorption where relative impermeability of the lungs to several drugs is posing a major obstacle after pulmonary delivery [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cyclodextrins are extensively used to improve the water-solubility of poorly water-soluble drugs. CD is reported as a safe excipient via oral, intravenous, and inhalation administration [ 11 , 12 ]. Beta-cyclodextrins (β-CDs) are the most frequently used cyclodextrins in pharmaceutical formulations, due to their ease of availability, cost effectiveness, and ability to readily form inclusion complexes with poorly water-soluble drugs [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…While this serum concentration was moderate, average maximal wet lung tissue concentration obtained at postmortem examination following inhalation of the same dose of tetrandrine was over 90 µg/g (~240 µmo/L if lung is treated as 60% water 68 ). 69 Lung concentrations following intravenous administration of 7.5 mg/kg were also relatively high with an average maximal concentration of ~20 µg/g (~53 µmol/L) 69 . In another study investigating the spatiotemporal distribution of tetrandrine in rats using mass spectrometry imaging, 30 mg/kg intravenous administration also resulted in high drug concentrations specifically in the lungs with a peak of ~120 µg/g (~321 µmol/L) 70 …”
Section: Administration and Dosagementioning
confidence: 99%
“…Su et al [ 147 ] prepared an NEB of TET-HP-β-CD, which used tetrandrine to prevent the fibroblasts proliferation, collagen synthesis and reverse fibrosis to treat IPF. Compared to the injection, it can reduce systemic exposure of the drug and toxic and side effects, reduce the number of administrations and increase patient compliance.…”
Section: Pulmonary Drug Delivery System For Tcm To Treat Ipfmentioning
confidence: 99%